Clinical pharmacology of tramadol and tapentadol, and their therapeutic efficacy in different models of acute and chronic pain in dogs and cats - Oliva, Adriana Domínguez; Alvarado, Alejandro Casas; Cortés, Agatha Elisa Miranda; Avalos, Ismael Hernández (Journal of Advanced Veterinary and Animal Research, 2021)
Opioids are considered the gold standard to manage acute or chronic or mild to severe pain. Tramadol is a widely prescribed analgesic drug for dogs and cats; it has a synthetic partial agonism on μ-opioid receptors and inhibits the reuptake of norepinephrine and serotonin. However, the biotransformation and resultant metabolites differ between species and depend on cytochrome P450 interactions. Dogs mainly produce the inactive N-desmethyl tramadol metabolite, whereas cats exhibit an improved antinociceptive effect owing to rapid active O-desmethyltramadol metabolite production and a longer elimination half-life. Tapentadol, a novel opioid with dual action on μ-receptors and noradrenaline reuptake inhibitory activity, is a promising option in dogs, as it is less reliant on metabolic activation and is unaffected by cytochrome polymorphisms. Although scientific evidence on the analgesic activity of tapentadol in both species remains limited, experimental studies indicate potential benefits in animals. This review summarizes and compares the pharmacology, pharmacokinetics, and therapeutic efficacy of tramadol and tapentadol in dogs and cats with different pain conditions. According to the available data, tramadol seems a more suitable therapeutic option for cats and should preferably be used as a component of multimodal analgesia in both species, particularly dogs. Tapentadol might possess a superior analgesic profile in small animals, but additional studies are required to comprehensively evaluate the activity of this opioid to manage pain in dogs and cats. J. Adv. Vet. Anim. Res., 8(2): 404-422, June 2021 http://doi.org/10.5455/javar.2021.h529